HUMAN RIGHTS PROTECTION IN ARTIFICIAL INTELLIGENCE GOVERNANCE: COMPARATIVE LESSONS FOR INDONESIA’S REGULATORY FRAMEWORK - Adhika Mahindra Satya; Radian Salman; Rosa Ristawati; Haryono Haryono; Ahmad Shabudin Ariffin (Diponegoro Law Review, 2026)
The rapid development of artificial intelligence (AI) has raised significant concerns regarding the protection of human rights, particularly in relation to privacy, non-discrimination, accountability, and legal certainty. This study examines regulatory gaps in Indonesia’s AI governance from a human rights perspective and proposes regulatory recommendations through a comparative analysis of legal frameworks in the European Union (EU), China, and the United States (U.S.). Employing doctrinal legal research, this study applies statutory, conceptual, comparative, and case-based approaches. The findings reveal that, although Indonesia has adopted several legal instruments relevant to digital technologies, including the Electronic Information and Transactions Law and its amendments, the Personal Data Protection Law, and various ethical guidelines, these instruments were not specifically designed to address the distinctive risks associated with AI systems. In particular, the absence of clear AI-specific definitions, risk-classification mechanisms, algorithmic transparency and audit requirements, mandatory human oversight, and rules on synthetic-content labeling creates substantial regulatory gaps that may undermine effective human rights protection. Comparative analysis indicates that Indonesia could draw on the EU AI Act’s risk-based regulatory framework, human oversight requirements, and transparency obligations; China’s approach to algorithm governance and synthetic-content labeling; and the U.S. sectoral model, particularly the Colorado AI Act and state privacy laws addressing transparency and discriminatory outcomes in automated decision-making. This study argues that Indonesia should establish a dedicated AI regulatory framework incorporating clear legal definitions, risk-based classification, algorithmic auditing, meaningful human oversight, transparency requirements, and synthetic-content labeling. Such a framework is essential to ensure that the development and deployment of AI systems remain consistent with human rights protection and legal certainty within Indonesia’s national legal order.